2020
DOI: 10.1186/s42506-020-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

Fungal and parasitic contamination of indoor public swimming pools in Arak, Iran

Abstract: Background: Swimming is a popular exercise for different types of people at different ages. Public swimming pools are places where fungal infections can be easily transferred. The purpose of this study is to evaluate the quality of mycological, parasitological, and physicochemical parameters of swimming pools of Arak city. Methods: This cross-sectional study was done for 12 months from April 2013 to March 2014 in six indoor active swimming pools of Arak city (A, B, C, D, E, and F). Samples were collected in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…For example, Sabouraud dextrose agar (SDA) is a commonly used medium for fungi especially for filamentous fungi [21,22], while blood agar (BA) and chocolate agar (CA) are used for fungi isolated from mycotic keratitis patients [21]. CHROMagarTM Candida medium has been used for Candida separation [23,24], whereas ID fungi plate culture with matrixassisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) is suitable for pathogenic filamentous fungi [25]. Obviously, cultivation of fungi is the most direct method with visualization of fungal morphology and colony color.…”
Section: Culture-dependent Methodsmentioning
confidence: 99%
“…For example, Sabouraud dextrose agar (SDA) is a commonly used medium for fungi especially for filamentous fungi [21,22], while blood agar (BA) and chocolate agar (CA) are used for fungi isolated from mycotic keratitis patients [21]. CHROMagarTM Candida medium has been used for Candida separation [23,24], whereas ID fungi plate culture with matrixassisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) is suitable for pathogenic filamentous fungi [25]. Obviously, cultivation of fungi is the most direct method with visualization of fungal morphology and colony color.…”
Section: Culture-dependent Methodsmentioning
confidence: 99%
“…In 2017, Mafi [58] reported 24% as a rate for Acanthameba spp. in pool water and amusement parks' pool; meanwhile Solgi et al and Sarmadian et al [59,60], revealed percentages of 20% and 16.7% respectively, in swimming pools. The difference in these studies was attributed to an increase in the water temperature of hot springs.…”
Section: Discussionmentioning
confidence: 94%
“… El-Badry et al 2020 Egypt Swimming pool (7) 28 0 Morphology, PCR Esboei et al ( 2020 ) Iran Swimming pools 30 12 Morphology, PCR Acanthamoeba T4 Latifi et al ( 2020 ) Iran Hot spring and beach 81 54 Morphology, PCR Acanthamoeba (T3, T4 e T5), V. vermiformis , and Naegleria spp. Paknejad et al ( 2020 ) Iran Swimming pool and bathtub 166 31 Morphology, PCR Acanthamoeba T3, Acanthamoeba T4, Acanthamoeba T11, Acanthamoeba sp., Protacanthamoeba bohemica , and N. lovaniensis Sarmadian et al ( 2020 ) Iran Swimming pool (6) 6 1 Morphology Acanthamoeba spp. Sarmadian et al ( 2020 ) Iran Swimming pool (6) 576 1 Morphology Acanthamoeba spp.…”
Section: Resultsmentioning
confidence: 99%
“… Paknejad et al ( 2020 ) Iran Swimming pool and bathtub 166 31 Morphology, PCR Acanthamoeba T3, Acanthamoeba T4, Acanthamoeba T11, Acanthamoeba sp., Protacanthamoeba bohemica , and N. lovaniensis Sarmadian et al ( 2020 ) Iran Swimming pool (6) 6 1 Morphology Acanthamoeba spp. Sarmadian et al ( 2020 ) Iran Swimming pool (6) 576 1 Morphology Acanthamoeba spp. Zeybek and Türkmen 2020 Turkey Swimming pool 25 7 Morphology, FISH Aykur and Dagci ( 2021 ) Turkey Swimming pool 26 3 PCR Acanthamoeba T2, T4, and T5 Bakri et al 2021 Saudi Arabia Swimming pool 10 4 Morphology, PCR Acanthamoeba spp.…”
Section: Resultsmentioning
confidence: 99%